"Working for the Nation" : diasporic youth and the construction of belonging in the Rwandan capital. - Bangerezako, Haydee (My University, 2013)
Scholarship on youth in Africa has mostly focused on unemployed young people, portraying them as a lost generation and exploring how states have failed them. Literature on young employed Africans has been conspicuously absent. This research portrays how a group of young professional Rwandans who define themselves as “diaspora” living in post-genocide Kigali, are redefining national belonging in economic terms. Many young professionals have moved from the diaspora to Rwanda because the state offers them a platform where they can find employment or start their own business: an entrepreneurial citizenship. The city of Kigali is experiencing physical and social transformation, and these young professionals are driving such change. The young people in this study see Rwanda as a place where they can belong by being cosmopolitan, and especially by becoming entrepreneurs. They feel that in Rwanda they are able to be global citizens more easily than in the Diaspora. This feeling of global citizenship is, ironically, what inspires in them a sense of national identity. This research explores the youth in the broader sense of economic activity and time and their sense of belonging in everyday life, in the capital city of Kigali.
Keywords: Ethnicity--Rwanda.; Youth--Rwanda.; Return migration--Rwanda.; Rwanda--History--Civil War, 1994.; Rwanda--Economic conditions.